Advances in accounting education. volume 28 : teaching and curriculum innovations - Calderon, Thomas G. (Emerald Publishing Limited, 2024)
Advances in Accounting Education: Teaching and Curriculum Innovations publishes both non-empirical and empirical articles dealing with accounting education. All articles emphasize teaching, learning and curriculum development, and discuss vital matters pertaining to the improvement of accounting programs at colleges and universities. Non-empirical papers are academically rigorous, and specifically discuss the institutional context of a course or program, as well as any relevant tradeoffs or policy issues. Empirical reports exhibit sound research design and execution, and develop a thorough motivation and literature review, including references from outside the accounting field, where appropriate. The 28th volume features 11 peer-reviewed papers surrounding four themes: (1) data science and analytics in accounting; (2) innovative teaching cases in taxation; (3) pipeline issues and the CPA exam; and (4) perspectives on accounting theory & integrated thinking and learning. Faculty with an interest in accounting education as well as accounting program administrators should find all three themes to be highly informative and interesting. Some practitioners and regulators in the accounting profession may also find useful policy-related nuggets in Volume 28.